ANALISIS PENGARUH RASIO KEUANGAN DAN INFLASI TERHADAP PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA PERIODE 2020-2024 - Muslimin Muslimin (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2025)
This study aims to examine the influence of internal and external factors on the profitability of Indonesian Sharia Rural Banks (BPRS). The internal factors used are non-performing financing (NPF), financing to deposit ratio (FDR), capital adequacy ratio (CAR), and operating expenses to operating income (BOPO). Meanwhile, the external factor used is inflation. This is a quantitative study using secondary data in the form of monthly time series data from 2020 to 2024, with the research object being Indonesian Sharia Rural Banks (BPRS). The research method used multiple linear regression analysis. The results show that the non-performing financing (NPF) variable does not have a significant effect on profitability (ROA). Additionally, inflation does not have a significant effect on the profitability of Indonesian BPRS. However, the financing to deposit ratio (FDR) variable has a positive and significant effect on the profitability of Indonesian BPRS. Furthermore, the capital adequacy ratio (CAR) variable has a significant positive effect on the profitability of BPRS Indonesia. The operational cost to operational income ratio (BOPO) variable has a significant negative effect on the profitability of BPRS Indonesia. Keywords : ROA; NPF; FDR; CAR; BOPO; Inflasi